Iron (Fe) content of rice (Oryza sativa) cultivated in a magnetite mined area in Brgy. Maya, MacArthur, Leyte - Apostol, Ma. Hazel Rosary C.; Corales, Olga G. (2016)
This study was conducted to assess the iron concentrations in rice plants (Oryza sativa) cultivated in two sites situated in a magnetite mined area in Brgy. Maya, MacArthur, Leyte. The iron concentration present in the rice plants was detected using atomic absorption spectrophotometer (AAS). Results showed that the iron concentration levels in Site 1 and Site 2 were significantly different from each other. The mean iron concentration in Site 1, which is 103.183 mg/kg to 193.733 mg/kg, lies within the normal range. While in Site 2, the iron uptake by the rice plants were deficient with a range of 48.900 mg/kg-50.300 mg/kg only. In addition, the soil pH in Site 1 and Site 2 range from 4.603-5.087 and 5.300-5.567, respectively. The soil organic content for Site 1 is 37.333%- 44.667% and for Site 2 is 14.667%- 15.333%.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Science and technology